ANALISIS RISIKO KESEHATAN PAJANAN BENZENE PADA PEKERJA DI BAGIAN LABORATORIUM INDUSTRI PENGOLAHAN MINYAK BUMI - Dewi Kartikasari; Nurjazuli Nurjazuli; Mursid Rahadjo (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Benzene (C6H6) is a compound produced from petroleum distillation process. Workers in the laboratories of petroleum revinery unit industry are individuals at risk due to exposure to benzene. The purpose of this research is to estimate the health risks of benzene exposures mainly via inhalation in continuous time. This research did at laboratory of PT. Pertamina RU IV Cilacap. This research was descriptive research with environmental health risks analysis method. Total sample were 51 respondents. Benzene concentration measurements was at 8 points in laboratory. The anthropometric characteristics include weight gain, long exposure, exposure frequency, and duration of exposure. The measures include the analysis of hazard identification, dose-response analysis, exposure analysis, risk characteristics, and risk management. The results of the average concentration of benzene from 8 point was 0,287 mg/m3. The average yield intake of all workers on non-carcinogenic effects was 0.0027 mg/kg/day. The average of workers intakes of carcinogenic effect was 0.0039 mg/kg/day. A total of 19 respondents (37.35) had risk of non-carcinogenic effects (because RQ> 1) in realtime exposure and 100% were risk on lifetime exposure. At the carcinogenic effects 20 respondents (39.2%) had a risk of carcinogenic effect (because ECR>10-4) in realtime exposure and 100% were risk on lifetime exposure. Levels of benzene in the air environment of the lab in 2016 may lead to non- cancer health risks and cancer . It is necessary to risk management by reducing the concentration of benzene , reducing the length of exposure , reducing the frequency of exposure , or reducing the duration of exposure.